Chemerin/ChemR23 axis promotes inflammation of glomerular endothelial cells in diabetic nephropathy. Issue 5 (19th February 2019) - Shang, Jin; Wang, Luyao; Zhang, Ya; Zhang, Shiyi; Ning, Lina; Zhao, Jifang; Cheng, Genyang; Liu, Dong; Xiao, Jing; Zhao, Zhanzheng
Abstract: Diabetic nephropathy (DN) is characterized by inflammation of renal tissue. Glomerular endothelial cells (GEnCs) play an important role in inflammation and protein leakage in urine in DN patients. Chemerin and its receptor ChemR23 are inducers of inflammation. The aim of this study was to investigate the function of chemerin/ChemR23 in GEnCs of DN patients. Immunohistochemical staining and qRT‐PCR were used to measure the expression of chemerin, ChemR23 and inflammatory factors in renal tissues of DN patients. Db/db mice were used as animal model. ChemR23 of DN mice was knocked down by injecting LV3‐shRNA into tail vein. Inflammation, physiological and pathological changes in each group was measured. GEnCs were cultured as an in vitro model to study potential signalling pathways. Results showed that expression of chemerin, ChemR23 and inflammatory factors increased in DN patients and mice. LV3‐shRNA alleviated renal damage and inflammation in DN mice. GEnCs stimulated by glucose showed increased chemerin, ChemR23 and inflammatory factors and decreased endothelial marker CD31. Both LV3‐shRNA and SB203580 (p38 MAPK inhibitor) attenuated chemerin‐induced inflammation and injury in GEnCs. Taken together, chemerin/ChemR23 axis played an important role in endothelial injury and inflammation in DN via the p38 MAPK signalling pathway. Suppression of ChemR23 alleviated DN damage.